(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Application offloading is a software-level technique for enhancing the compute capabilities of smart mobile devices in mobile cloud computing. The use of additional computational resources in the deployment and administration of VM on Smartphone is a problematic component of such frameworks. Virtual Machine (VM) deployment necessitates the use of computational resources for VM construction and configuration. The administration of virtual machines (VMs) involves computer resource usage, VM lifecycle monitoring, and physical resource management for VMs on smartphones. The goal of this project is to ensure that virtual machine deployment and administration do not necessitate additional processing resources on mobile devices for application offloading. VM deployment, application execution times, and the simulation’s total execution time are used to evaluate the success of VM deployment and management in application processing. VM deployment and management, according to the research, need additional resources on the computer host. As a result, deploying virtual machines on smart mobile devices has become a heavyweight technique for offloading processes.